Agreement Between County of Ventura and City of Oxnard Pertaining to Airport Development and Surrounding Area (1980)
An agreement between Ventura County and Oxnard outlining the rights of each in regards to Oxnard Airport. Includes restrictions that are to be imposed on Oxnard Airport.